PENDAMPINGAN PROSES PRODUKSI, PENERAPAN GMP (GOOD MANUFACTURING PRACTICES) SERTA PENDUGAAN MASA SIMPAN KERIPIK PISANG AGUNG UMKM JAPA DESA GADINGKULON - Rosalia Rachma Oktavianasari; Arya Paksi M; Baharuddin Jamil A.M; Revi Safrita; Zalva Adinda Z.P (LPPM ITB AAS Indonesia Surakarta, 2022)
Community Services is one of the applications of responsibility as a student stated in the Tri Dharma of University in the form of publics empowerment with the purpose of giving solutions to problems in the publics without expecting anything in return. One purpose of community services is by giving accompaniment to JAPA UMKM in the publics community. JAPA UMKM is one of the UMKM is located in Malang Regency which produces banana chips of the Great Banana type. JAPA UMKM is located in Princi, RT 02 RW 04 Gadingkulon Village, Dau, Malang Regency, East Java. This JAPA UMKM assistance purpose is provide solutions, evaluations and improvements to the problems that exist in JAPA UMKM including of the production system, application of GMP and estimation of shelf life. The solutions and improvements that we have made at JAPA UMKM are assisting the production process from raw materials to finished products, implementing the GMP (Good Manufacturing Practices) process for JAPA UMKM, calculating the estimated shelf life of banana chips and assisting the packaging process of banana chips JAPA UMKM